The effect of arm position on strength of pull in freestyle and backstroke - Higgs, S. L.; Gallagher, H. (Swimming Technique, 1979)
The strength of arm pull positions in both freestyle and backstroke were measured on age-group swimmers (15 males and 15 females). The measurements were taken in pre-determined positions, the athlete being strapped to a strength table edge with the right arm hanging free. It was found that when a swimmer pulled "wide" in relation to the midline of the body that strength was greatest. There was no difference in pulling strength between male and female swimmers averaging 13 years of age. This article demonstrates a problem that can occur with research. Tests have been conducted out of the water in an unnatural position and results extrapolated to actions in the water. As well, a coaching bias is demonstrated when swimmers as far back as the 1920s (e.g., Johnny Weissmuller) are used to verify the authors' assertions of the benefits of swimming with flat shoulders. It is now known that reducing shoulder roll is particularly disadvantageous in both freestyle and backstroke so that advocacy is incorrect. Being flat is also supposed to reduce resistance. That assertion is remarkable for it is the frontal cross-sectional area and body surface that is the major cause of resistance in swimming, features which are independent of whether a swimmer is flat or rolling. Implication: There is something which can be gained from this erroneously reported item. The action of "pulling wide" in relation to the shoulder is important for it places the arm in good position to use muscles in the front and back of the chest (e.g., the sternocostal section of the pectoralis major, the latissimus dorsi, and teres major). If one were to pull the arm under the body while keeping a flat shoulder position the effect of these muscles on the pull would be reduced. This article can be used to support the benefits of a wide pull in relation to the shoulder girth. When that girth is rotated through at least 90 degrees and the pull is wide, then the arm action that is demonstrated will center around the longitudinal axis and produce forces that are strongest and the most direct for swimming.